Adult Attachment Styles and Marital Conflict Resolution Styles among Couples in Nairobi,Kenya - Mburu, Lucy Wambui (PAC University, 2022)
Human beings have been shown to have styles that they employ in handling certain aspects of their relational lives. Specific categories of styles sometimes relate with each other under certain circumstances, affecting outcomes in relationships. There is a gap in research that this study sought to fill in showing how Adult Attachment Styles (AAS) and also certain demographic characteristics relate with the Marital Conflict Resolution Styles (MCRS)employed by couples in Nairobi, Kenya. The specific objectives of the study were: to find out the AAS of married individuals in Nairobi County, to investigate the marital conflict resolution styles employed by couples in Nairobi County, to establish how certain demographics influence the marital conflict resolution styles of couples, and to examine how the AAS relate with MCRS among couples in Nairobi County. This study was informed bythe attachment theory and Gottman’s marital conflict styles theory. The study adopted the correlation research design. Six CITAM assemblies that are located in Nairobi County were purposively selected for participation. The individuals that took part were selected using simple random and snowballing sampling methods. The quantitative data for finding out theAAS and marital conflict resolution styles was collected using the standardized questionnaires. Six semi-structured interviews were additionally conducted with pastors in charge of Family Care and Enrichment from the participating assemblies. Pearson correlation coefficient factor was used to determine the relationship between causes of conflicts, demographics and AAS, with marital conflict resolution styles. All tests of significance were computed at a significant level of 5% with the help of SPSS. The descriptive statistics used were percentages, mean and k-means non-hierarchical cluster analysis. The inferential statistics used were Chi-square test and ANOVA. The key findings of this study showed a significant association between AAS and marital conflict resolution styles. In addition, age, marital longevity, level of education, level of income, and the cause of a marital conflict had a significant influence on the marital conflict resolution styles of the respondents. Gender and occupation of participants showed no statistically significant influence on any of the marital conflict resolution styles in the study. These findings demonstrate that AAS and certain demographics have an influence on the marital conflict resolution styles that couples employ. Facilitators of premarital counseling classes, marriage therapists as well as pastors need to be aware of these influences while helping couples to handle conflicts constructively.
Keywords: Adult Attachment styles; Marital conflict; Resolution Styles; Among couples; Pre marital counselling